Postgraduate education prospects of the development of continuing professional education in rheumatology - Elena Andreyevna Galushko; E L Nasonov (Современная ревматология, 2014)
A comprehensive program for continuing professional education of rheumatologists «Education throughout Life» was elaborated in 2013 under the auspices of the All-Russian public organization «Russian Association of Rheumatologists» (RAR) and V.A. Nasonova Research Institute of Rheumatology, Russian Academy of Medical Sciences. The program includes implementation of additional forms of educational activity and elaboration of new learning models based on modern telecommunication information technologies. Personified analysis of the acquired knowledge and skills and continuity of the learning process (including the distance education methods) are the mandatory conditions to fulfil the program. Each physician has to earn at least 50 credits annually (a total of 250 credits throughout the 5-year course). The proportion between the remote and resident classes is set depending on the curriculum of the basic cycles for postgraduate education in rheumatology. Under this program, the RAR participates more actively in elaboration and certification of the programs for professional education in rheumatology, as well as other types of educational activity.